Energy and mass in relativity theory - Okun Lev B (World Scientific, 2009)
This is the first book in which Einstein's equation is explicitly compared with its popular though not correct counterpart E = mc2, according to which mass increases with velocity. The book will be of interest to researchers in theoretical, atomic and nuclear physics, to historians of science as well as to students and teachers interested in relativity theory.
Keywords: Mass -Physics; Special relativity -Physics